UTANG PIUTANG DALAM PERSPEKTIF EKONOMI ISLAM - Tri Nadhirotur Rofi'ah; Nurul Fadila (Faculty of Islamic Economics and Business, 2021)
The practice of accounts payable transactions as one aspect of fulfilling one's life through social interactions. A transaction that is full of privileges and virtues that Allah has promised for the doer (the creditor). The practice of accounts payable that we know, in addition to having a positive side through the principle of please help, but often it is also a starting point for disputes and enmity between humans. This will become evident when in practice, humans ignore some of the fundamental principles that form the framework for legalizing the practice of helping to help; namely honesty.